Global migrations: Reflections for forensic anthropology (Research, Society and Development, 2025)
The present study aimed to understand the extent to which current global migration flows may influence the methods used for human identification in forensic anthropology, especially those related to the biological profile pillar that deals with population affinity. This review adopts a theoretical and documentary approach. Reports and statistical data from international organizations were analyzed, and articles were searched in the PubMed, Scopus, and Web of Science databases. The article search strategies employed a combination of terms related to the main concepts: Migration, forensic anthropology, biological profile, and population diversity. Armed conflicts, climate change, economic crises, and globalization drive migration flows. In recent years, there has been a significant increase in these flows, with Europe receiving the largest number of migrants. This intensification of human mobility presents substantial challenges to traditional methods of biological profiling used in forensic anthropology, particularly for estimating population affinity, due to the inadequacy of reference databases, the complexities of genetic admixture, and conceptual and ethical controversies surrounding the categorization of human variation.  Thus, the evolving patterns of global migration will require forensic anthropologists to adapt their practices, employing multidisciplinary approaches and refining identification methods to increase the accuracy and reliability of forensic analyses.  These are not only scientific challenges but also ethical imperatives to ensure that the discipline can continue to fulfill its vital role in human identification in an increasingly interconnected and mobile world..